2022
DOI: 10.1007/s00521-022-07096-6
|View full text |Cite
|
Sign up to set email alerts
|

Evading behavioral classifiers: a comprehensive analysis on evading ransomware detection techniques

Abstract: Recent progress in machine learning has led to promising results in behavioral malware detection. Behavioral modeling identifies malicious processes via features derived by their runtime behavior. Behavioral features hold great promise as they are intrinsically related to the functioning of each malware, and are therefore considered difficult to evade. Indeed, while a significant amount of results exists on evasion of static malware features, evasion of dynamic features has seen limited work. This paper examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…One suggested approach is to further encode the encrypted files in a way as to reduce their overall entropy value, by for example, using base64 encoding. However, despite this theoretical mitigation technique, crypto-ransomware techniques are still being proposed that utilise entropy calculations as part of their design [ 21 , 75 , 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…One suggested approach is to further encode the encrypted files in a way as to reduce their overall entropy value, by for example, using base64 encoding. However, despite this theoretical mitigation technique, crypto-ransomware techniques are still being proposed that utilise entropy calculations as part of their design [ 21 , 75 , 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since many ransomware detectors follow a similar process-based approach, a relevant research question is whether they exhibit similar vulnerabilities. Recently, in [8], the authors proposed a novel family of evasion attacks against processbased ransomware detectors. Specifically, the authors suggested three attacks: process splitting, functional splitting, and mimicry attack.…”
Section: Evasive Ransomware: Cerberusmentioning
confidence: 99%
“…The more powerful functional splitting attack generates a smaller number of processes, each performing few types of operations (such as performing only file reads or file writes). While this attack is practical, it can be mitigated with adversarial training [8]. Finally, the mimicry attack works by splitting ransomware into multiple processes, each mimicking the behavioral profile of benign applications from the point of view of disk operations.…”
Section: Evasive Ransomware: Cerberusmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, there is no clear understanding of how these approaches: (i) fare on a variety of compressed file formats and sizes, and (ii) compare to each other. The potential negative implications are significant: the use of ineffective techniques for identifying encrypted content can hinder the effectiveness of ransomware detectors [17,18], and significantly limit the capability of forensic tools.…”
Section: Introductionmentioning
confidence: 99%